Global Geographies of Offshore Campuses - Jana M. Kleibert; Alice Bobée; Tim Rottleb; Marc Schulze (Leibniz-Institut für Raumbezogene Sozialforschung (IRS), 2020)
The internationalisation of higher education institutions has received much attention. Our report presents new data on the geographies of the physical presences of universities, or offshore campuses, around the world while in particular focussing on the urban scale. While globalisation is increasingly coming under political pressure, our figures show an uninterrupted rise in the number of physical presences and an increasing diversification of universities' countries of origin as well as their locations abroad.
Keywords: 710